Early therapeutic efficacy of condoliase chemonucleolysis for lumbar disc herniation - Kazuyoshi Kobayashi; Koji Sato; Yoshinori Morita (Journal of Orthopaedic Surgery and Research)
Abstract Background Low back pain is often caused by lumbar disc herniation (LDH). Treatment of LDH is possible using chemonucleolysis of the nucleus pulposus with condoliase injection. However, onset of the therapeutic effect varies among patients, with improvement from an early stage to 3 months post-injection. This study was performed to identify the characteristics of early responders to condoliase therapy. Methods A retrospective cohort study was performed in 371 consecutive patients (259 males, 112 females; age, 49.9 ± 18.7 years; follow-up period, 13.1 ± 7.4 months) treated with condoliase injection for LDH between August 2018 and January 2024. Chemonucleolysis was performed with 1 mL of condoliase (1.25 U/mL) injected into the intervertebral nucleus pulposus. Clinical assessments were made before injection and 1 day, and 1, 4 and 12 weeks post-injection. Pain was measured on a visual analogue scale. Herniation parameters were evaluated on axial MRI. The herniated disc volume was measured on plain lumbar radiography. Demographic and clinical data were taken from medical charts. Multivariate logistic regression analysis was used to identify factors with independent relationships with treatment efficacy. Results Improvement of leg pain from baseline by ≥ 50% occurred in 21% of cases within one day after condoliase treatment. Patients with this improvement at 1 week post-injection were defined as early responders (n = 142, 38.3%). In multivariate analysis, age < 40 years (p = 0.022, odds ratio (OR): 1.71, 95% confidence interval (CI): 1.12–4.35), Pfirrmann Grade II or III at baseline (p = 0.032, OR: 1.86, 95% CI: 1.17–5.41), and a high intensity MRI signal in the herniation (p = 0.041, OR: 1.87, 95% CI: 1.06–5.27) were significantly associated with early improvement. No patients had anaphylactic shock or neurologic sequelae. Conclusions This study confirms the safety and efficacy of chemonucleolysis with condoliase for treating patients with painful LDH. Age, high-intensity MRI signals, and baseline Pfirrmann grade were significant factors associated with early improvement.